2018
DOI: 10.1016/j.rbmo.2017.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Patients with a high proportion of immature and meiotically resistant oocytes experience defective nuclear oocyte maturation patterns and impaired pregnancy outcomes

Abstract: Patients presenting with abnormally high numbers of immature oocytes at retrieval are more likely to exhibit maturation resistant oocytes. However, the clinical relevance of such events remains unknown. We investigated nuclear maturation competence of immature oocytes from patients showing >40% of collected immature oocytes (Study group) and Controls, in which a normal number of mature oocytes (≥60%) was retrieved. Following in-vitro culture, oocytes were classified as maturation resistant or in-vitro matured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We agree with assumption of other authors that these cases represent intrinsic oocyte problems not influenced by the follicular environment and in vitro maturation media cannot be designed to overcome intrinsic causes of maturation arrest [15]. Although mature oocytes can be obtained after extended in vitro culture of denuded GV oocytes in patients with a high proportion of immature and meiotically resistant oocytes after COS and hCG triggering, this so-called rescue IVM strategy should be considered with caution, as oocytes that reach metaphase II after rescue IVM have a significantly higher percentage of spindle abnormalities and misaligned chromosomes [30].…”
Section: Discussionmentioning
confidence: 99%
“…We agree with assumption of other authors that these cases represent intrinsic oocyte problems not influenced by the follicular environment and in vitro maturation media cannot be designed to overcome intrinsic causes of maturation arrest [15]. Although mature oocytes can be obtained after extended in vitro culture of denuded GV oocytes in patients with a high proportion of immature and meiotically resistant oocytes after COS and hCG triggering, this so-called rescue IVM strategy should be considered with caution, as oocytes that reach metaphase II after rescue IVM have a significantly higher percentage of spindle abnormalities and misaligned chromosomes [30].…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this response may represent the amount of intracellular calcium in the ER as well as the channel activity which is responsible for regulating calcium entry into the cells. [ 40 ]…”
Section: Discussionmentioning
confidence: 99%
“…Evaluation of cytoplasmic maturity with immunocytochemical methods revealed that metaphase plate rearrangements are more frequent in oocytes showing immaturity [70]. Another study investigated abnormal maturation in patients with a high proportion of immature oocytes [71].…”
Section: Cytoplasmic Maturationmentioning
confidence: 99%